2015
DOI: 10.1590/1809-9823.2015.13180
|View full text |Cite
|
Sign up to set email alerts
|

Dupla tarefa e mobilidade funcional de idosos ativos

Abstract: Palavras-chaves:Envelhecimento. Acidentes por Quedas. Tarefa de Controle Duplo. Idoso. ResumoIntrodução: Define-se "dupla tarefa" como a capacidade de efetivar uma ação primordial incorporada a uma segunda atividade. Em idosos, é presumível que a execução de ações simultâneas comprometa o equilíbrio postural, favorecendo quedas nesta população. AbstractIntroduction: Dual task can be defined as the ability to perform a primary action embedded in a second activity. In the elderly, it is presumed that the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
10
0
10
Order By: Relevance
“…During the dual task TUG, participants followed the same above-mentioned protocol while speaking the days of the week in reverse order (e.g., Wednesday, Tuesday, Monday, Sunday, Saturday, Friday, Thursday, and so on until the test finished). The rationale for choosing this dual task was based on previous research (Barbosa et al, 2008;Fatori et al, 2015;Silva et al, 2017). They were instructed to start speaking, as quickly as-possible, while still sitting.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…During the dual task TUG, participants followed the same above-mentioned protocol while speaking the days of the week in reverse order (e.g., Wednesday, Tuesday, Monday, Sunday, Saturday, Friday, Thursday, and so on until the test finished). The rationale for choosing this dual task was based on previous research (Barbosa et al, 2008;Fatori et al, 2015;Silva et al, 2017). They were instructed to start speaking, as quickly as-possible, while still sitting.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This result is consistent with previous findings, since Iersel et al 19 observed in their study with elders of the community that, by adding motor and cognitive activities, it caused increased step and decreased gait speed. Corroborating results found, the study by Fatori et al 20 shows that individuals who performed the Timed up and Go, which is a standing and walking test associated with a dual task, took more time to perform it compared to the simple test. Speed reduction during dual task performance is an automatic adaptation effect of the body to reduce risk of falls in more complex situations 19 .…”
Section: Discussionmentioning
confidence: 56%
“…A associação entre dois fatores, sexo e idade, parece ser um importante determinante para perdas motoras mais acentuadas. A literatura vem demonstrando que o avanço da idade está associado à intensificação destas perdas, tanto relacionadas aos componentes neurológicos como osteomusculares (RUBIO et al, 2013;FATORI et al, 2015 Fatores como alterações hormonais e perdas em componentes físicos, que nas mulheres se iniciam já durante a meia-idade, refletem em um declínio mais acentuado nas funções motoras, tornando-se mais evidentes a partir dos 70 anos. Nos homens, essas alterações aparecem mais tardiamente e, dessa forma, as perdas motoras são menos evidentes quando comparadas às mulheres da mesma faixa etária (ABAD-DIEZ et al, 2014;ALEXANDRE et al, 2014).…”
Section: Discussionunclassified